PENGARUH MOTIVASI EKSTRINSIK DAN PRESTASI BELAJAR AKUNTANSI TERHADAP MINAT INVESTASI DAN KEPUTUSAN INVESTASI MAHASISWA FE PROGRAM STUDI AKUNTANSI UNESA - Sulistyowati, Nur Wahyuning (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aimed to analyze the effect of extrinsic motivation and academic achievement for investment interest and investment decisions study. The results showed that extrinsic motivation has direct significant effect on accounting learning achievement. Accounting learning achievement does not significantly influence the investment interest. Extrinsic motivation has significant effect on investment interest. investments Interest significantly influence investment decisions. accounting Learning achievement has significant effect on investment decisions, and extrinsic motivation significantly influence investment decisions. While extrinsic motivation indirectly has a significant influence on investment decisions through investment interest, so that the interest showed to mediate investment extrinsic motivation on student investment decisions, and learning achievement of accounting has a significant influence on investment decisions through investment interest, so that the investment interest shown to mediate the learning achievement of accounting student investment decisions. The findings in this study is that the investment interest plays an important role in investment decisions of students.